A Mechanically Actuating Carbon‐Nanotube Fiber in Response to Water and Moisture. (13th October 2015) - He, Sisi; Chen, Peining; Qiu, Longbin; Wang, Bingjie; Sun, Xuemei; Xu, Yifan; Peng, Huisheng
Abstract: A new family of hierarchically helical carbon‐nanotube fibers with many nano‐ and micro‐scale channels has been synthesized. They demonstrate remarkable mechanical actuations in response to water and moisture. The water or moisture is first rapidly transported through the trunk micron‐scale channels and then efficiently infiltrates into the interconnected capillary nanoscale channels, similar to the blood flow in our body. Therefore, rapid and large contraction and rotation of the fiber occurs with a high reversibility. These mechanically actuating fibers are promising for various applications, and smart windows and louvers have been investigated as two demonstrations. Abstract : Wassermelder : Hydrophile, hierarchisch helikale Fasern aus Kohlenstoffnanoröhren ziehen sich in Gegenwart von Wasser oder Feuchtigkeit schnell zusammen und rotieren, was auf das Vorliegen einer großen Zahl an Nano‐ und Mikrokanälen zurückzuführen ist. Die leichten, flexiblen und starken Fasern eignen sich für Anwendungen in intelligenten Schaltern, Aktuatoren, Robotern und biomimetischen Funktionseinheiten.